The construction of oligonucleotide-cycloastragenol and the renoprotective effect study - Tang, Lumin; Li, Xiang; Qin, Yu; Geng, Xinyao; Wang, Ruowen; Tan, Weihong; Mou, Shan (Frontiers in Bioengineering and Biotechnology, 2022)
Traditional Chinese Medicine (TCM) provides unique therapeutic effects for many diseases with identified efficacy during long practice. Astragalus Membranaceus (AM) is the Chinese herbal applied for kidney injury in the clinic, but it remains challenging to further enhance the efficacy. Cycloastragenol (CAG) is the ingredient isolated from AM with poor water solubility, which has shown a renoprotective effect. Herein we designed and synthesized the corresponding solid-phase module of CAG, from which CAG as a pharmaceutical element was incorporated into oligonucleotides (ON) as an ON-CAG conjugate in a programmable way by a DNA synthesizer. Cell viability study demonstrated that ON-CAG conjugate remains similar renoprotective effect as that of CAG, which efficiently recovers the activity of HK-2 cells pretreated with cisplatin. Similarly, in the renal cells treated with the conjugate, the biomarkers of kidney injury such as KIM-1 and IL-18 are downregulated, and cytokines are reduced as treated with anti-inflammatory agent. Overall, we have managed to incorporate a hydrophobic ingredient of TCM into ON and demonstrate the oligonucleotide synthesis technology as a unique approach for the mechanism study of TCM, which may facilitate the discovery of new therapeutics based on TCM.